Three by the sea - Marshall, Edward; Marshall, James, 1942- (New York : Dial Press, 1981)
Three friends relax after their picnic lunch by each telling his or her best story.
3 7 11 13 18 19 20 26 27 36
Keywords: Storytelling -- Fiction